The association between traumatic experience, paranoia and hallucinations: a test of the predictions of psychological models. - Gracie, A; Freeman, D; Green, S; Garety, P; Kuipers, E; Hardy, A; Ray, K; Dunn, G; Bebbington, P; Fowler, D (2007)
OBJECTIVE: The current study investigated the relationship between trauma and predisposition to hallucinations and to paranoia in a non-clinical sample. METHOD: A total of 228 students completed online measures of trauma, post traumatic stress disorder (PTSD), schematic beliefs, perceptual anomalies, and predisposition to hallucinations and paranoia. RESULTS: Associations were found between negative schematic beliefs, PTSD and predisposition to both paranoia and hallucinations. PTSD reexperiencing-symptoms were most strongly associated with a predisposition to hallucinations. Negative beliefs about self and others were most strongly associated with a predisposition to paranoia. CONCLUSION: The results provide support for the prediction that there may be two routes between trauma and predisposition to psychosis. Clear support was found for a link between trauma and psychosis mediated by negative beliefs about self and others. There may also be a direct association between re-experiencing symptoms and hallucinations.